INTEREST IN READING IMPROVES THE QUALITY OF BASIC EDUCATION - Eliyah; Eyad Saleh Bani-Domi (Adisam Publisher, 2023)
Teachers are role models for their students, exemplary behavior at school is total exemplification, not only with regard to normative matters but as a whole. Likewise with reading, the example set by teachers at school will continue to stick with children until they return home, until they grow up. Because children can learn from observations and experiences they go through. As one of the assumptions of social cognitive theory is,